Begonia â€œTuti Siregarâ€ (Begonia listada Smith &Wasshausen x Begonia acetosa Vellozo): a new cultivar from Bali Botanic Garden, Indonesia - HARTUTININGSIH M. SIREGAR; I MADE ARDAKA; MUSTAID SIREGAR (Society for Indonesian Biodiversity, 2010)
SiregarHM, Ardaka IM, Siregar M (2010) Begonia â€œTuti Siregarâ€ (Begonia listada Smith &Wasshausen x Begonia acetosa Vellozo): a new cultivar from Bali Botanic Garden, Indonesia. Biodiversitas 11: 15-18. A new Begonia cultivar was generated by crossing Begonia listada Smith & Wasshausen with Begonia acetosa Vellozo at Bali Botanic Garden began in 2005. The female flowers of B. listada were pollinated with pollen grains from B. acetosa. Begonia listada is characterized by the following characters: erect, non rhizomatous, branched subshrub to 1 m tall; leaves: blade above bronze, beneath purple with two pale green veins. B. acetosa has the following characters: creeping rhizomatous perennial to about 1 m tall; leaves: thick, blade above olive green, beneath bright red, both surfaceswith a dense covering of short stiff white hairs. The results of crossing is, herb, erect, non-rhizomatous, 40-75 cm height, stem brownish green, hairy, stipules in pairs, marcescent, ascending, membranous. Leaves, beautiful asymmetrical leaves intermediate between both parents; petiole deeply red, covered with wooly hairs, veins yellow like B. listada. The new cultivar, Begonia â€˜Tuti Siregarâ€™, has the American Begonia Society registration number 1001 (Salisbury 2008).Key words: Begonia â€œTuti Siregarâ€, Bali Botanic Garden, Indonesia, new cultivar.